SAE Technical Paper Series 2014
DOI: 10.4271/2014-01-0888
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Multiphysics Based Numerical Study to Predict Automotive Fuel Tank Sloshing Noise

Abstract: With significant decrease in the background noise in present day automobiles, liquid slosh noise from an automotive fuel tank is considered as a major irritant during acceleration and deceleration. All major international OEMs and their suppliers try to reduce sloshing noise by various design modifications in the fuel tank. However, most major activities reported in open literature are primarily based on performing various CAE and experimental studies in isolation. However, noise generation and its propagation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The volume of fluid method is an efficient multi-phase method used to simulate the flow of immiscible liquids [20]. This method examines the free surface movement during the liquid sloshing in the tank [4,40]. This method defines a function such as F to define the free surface position and capture the liquid volumes, and defines the volume fraction of a cell filled with liquid and defined by the ratio F = V liquid /V total volume .…”
Section: Modeling the Sloshing Motion Of A Partially Liquid-filled Fu...mentioning
confidence: 99%
“…The volume of fluid method is an efficient multi-phase method used to simulate the flow of immiscible liquids [20]. This method examines the free surface movement during the liquid sloshing in the tank [4,40]. This method defines a function such as F to define the free surface position and capture the liquid volumes, and defines the volume fraction of a cell filled with liquid and defined by the ratio F = V liquid /V total volume .…”
Section: Modeling the Sloshing Motion Of A Partially Liquid-filled Fu...mentioning
confidence: 99%
“…18.1). For realistic car models, several previous evaluations have shown that the two-equation k-ε turbulence closures have been successful in reasonably describing the aerodynamics properties on commercial vehicles [16][17][18][19] and more serve as a popular choice for Industrial flows [24,25]. Therefore, in this study, the two-equation turbulence models, namely the Standard k-ε and Realizable k-ε were considered and in addition, the one equation Spalart-Allmaras model was considered in further assessing the appropriateness of the predictions from the two-equation turbulence closures.…”
Section: Turbulence Modellingmentioning
confidence: 99%
“…Ganuga et al [28] established a three-dimensional, fully coupled FSI model, which revealed that the behavior of internal structures in a sloshing tank is subjected to resonance, highlighting the role of flexible baffles. Jadon et al [29] used an integrated experimental and multi-physics numerical approach to predict automotive fuel tank sloshing noise by simulating the fluid sloshing, dynamic forces, vibration displacement, and noise radiation. Zheng et al [30] proposed the ISPH method to accurately simulate violent sloshing with complex baffles, providing insights into effective engineering solutions for dampening sloshing and reducing impact pressures.…”
Section: Introductionmentioning
confidence: 99%